GxE interactions in genome-wide association studies - Conti, David V. (Henry Stewart Talks, 2016)
Biology of nicotine, Marginal tests, Case-control analysis, Case-only analysis, Empirical-Bayes weighted average, Bayes model averaging, Joint tests, Screening approaches, 2-step approaches
Archived at 2025/02/06